THE ROLE OF PERFORMANCE OF WATER USER FARMER ASSOCIATION (GHIPPA) RUKUN MAKMUR SEKUNDER BERINGIN IN THE DEVELOPMENT OF AGRICULTURE IN SIDOARJO REGENCY - Yusro, Achmad; Agustina, Isna Fitria (Journal of Geography, Regional Planning and Development, 2024)
General Background: Irrigation management is essential for successful agricultural development, particularly in regions like Kabupaten Sidoarjo, where efficient water resource management and equitable water distribution are critical issues. Effective irrigation management is necessary for sustainable farming practices, especially with limited water resources. Specific Background: In Kabupaten Sidoarjo, the establishment of Gabungan Himpunan Petani Pemakai Air (GHIPPA), or Water User Associations, aims to address these challenges by promoting participatory irrigation system management. However, despite this initiative, issues regarding efficient water resource management and fair distribution persist, indicating a need for more effective farmer involvement and empowerment in the irrigation process. Knowledge Gap: While the concept of participatory irrigation management has been widely discussed, there is limited research that specifically focuses on the level of farmer empowerment within GHIPPA in Kabupaten Sidoarjo. Furthermore, there is a lack of detailed studies examining the impact of farmer participation on irrigation management and the successful implementation of water resource management policies in the region. Aims: This study aims to assess the level of farmer empowerment within GHIPPA Rukun Makmur in Kabupaten Sidoarjo, based on the empowerment theory proposed by Susiladiharti (in Huraerah, 2011:90). The research seeks to evaluate the effectiveness of participatory irrigation management by examining key factors such as access to irrigation, awareness of agricultural needs, competence in participation, and involvement in policy evaluation. Results: The research found that farmer empowerment in GHIPPA Rukun Makmur meets all five levels of empowerment. These include: 1) meeting basic needs such as access to irrigation and understanding of network management, 2) control and access to the irrigation network, 3) awareness of the importance of planting seasons for effective water use, 4) competence in active participation, and 5) engagement in policy evaluation and recommendations. Novelty: This study provides a unique contribution by applying the empowerment theory to assess farmer participation in GHIPPA, offering insights into the practical implementation of participatory irrigation management in a specific regional context. Implications: The findings suggest that while farmer empowerment is progressing, there is a need for the Water Resource Sector of Dinas PUPR Kabupaten Sidoarjo to enhance personnel resources and implement more effective monitoring of land ownership changes. Regular extension programs are recommended to maintain and further improve farmer participation in irrigation management.